Watchmen (DC Modern Classics Edition) - Moore, Alan 1953- (DC Comics, 2018)
In an alternate world where the mere presence of American superheroes changed history, the US won the Vietnam War, Nixon is still president, and the cold war is in full effect. Watchmen begins as a murder-mystery, but soon unfolds into a planet-altering conspiracy. As the resolution comes to a head, the unlikely group of reunited heroes--Rorschach, Nite Owl, Silk Spectre, Dr. Manhattan and Ozymandias--have to test the limits of their convictions and ask themselves where the true line is between good and evil. Alan Moore and Dave Gibbons created Watchmen and changed the course of comics' history, essentially remaking how popular culture perceived the genre. It's no coincidence that this groundbreaking volume is the first of DC Modern Classics. DC Modern Classics features the most highly regarded graphic novels from the world's foremost authority on graphic literature. -- Amazon.com